Searching for Animal Names Through Games - Dicky Reza Edina Permana; Nurkhalis Suazi; Teguh Cahya Wibawa (International Journal of Research and Applied Technology (INJURATECH), 2022)
Children are the next generation of the nation where children must have provisions in the form of knowledge. And knowledge can be obtained through learning. The basic nature of children is playing with the introduction of these animal names through games. The purpose of this research is to create a mobile game for children aged 5-7 years that simulates animal name recognition. The research method used in this research is descriptive with a quantitative approach. The results of the research conducted so that children recognize the names of animals. The main concept of this product is game. In the end this game was created to educate children. This simulation is made for children to know the names of existing animals. The game scheme is made in several levels. This research was conducted with the aim of developing games so that they can be a means of learning for children on Android-based mobile devices, to broaden children's horizons, and to determine the feasibility of Android-based learning. With this game can shape the character and development of children.